2012
DOI: 10.1007/s10844-011-0192-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive two-level optimization for selection predicates of multiple continuous queries

Abstract: A data stream is a massive unbounded sequence of data elements continuously generated at a rapid rate. Query processing for such a data stream should also be continuous and rapid, which requires strict time and space constraints. In order to guarantee these constraints, we have proposed a new scheme called an Attribute Selection Construct (ASC) for an attribute of a data stream in our previous study (Lee and Lee, Information Sciences 178:2416-2432, 2008. As its optimization technique, this paper proposes the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It also additionally explained that the awareness effect works but the persuasive effect does not influence on consumers. A study in Korean film market examining the role of eWOM compared movie reviews in Internet portal website and tweets in Twitter, and showed that both tweets and movie reviews have the significant effect of eWOM [21]. The study used several variables such as released screens, average ratings, number of ratings, number of tweets, and revenues for analyzing eWOM effect, but sentiment of reviews and tweets did not considered to the analysis model.…”
Section: Ewom Analysis In Film Marketmentioning
confidence: 99%
“…It also additionally explained that the awareness effect works but the persuasive effect does not influence on consumers. A study in Korean film market examining the role of eWOM compared movie reviews in Internet portal website and tweets in Twitter, and showed that both tweets and movie reviews have the significant effect of eWOM [21]. The study used several variables such as released screens, average ratings, number of ratings, number of tweets, and revenues for analyzing eWOM effect, but sentiment of reviews and tweets did not considered to the analysis model.…”
Section: Ewom Analysis In Film Marketmentioning
confidence: 99%